Prediction of Rehabilitation Nurses’ Psychological Well-Being by Personality Traits and Defense Mechanisms - Morteza Ghadimianfar; Asghar Dadkhah (Iranian Rehabilitation Journal, 2015)
Objectives: The purpose of the study is to predict the psychological well-being of nurses based on personality traits and defense mechanisms.